2013
DOI: 10.1016/j.recli.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e práticas preventivas em infertilidade entre mulheres atendidas em um serviço público de saúde

Abstract: r e p r o d c l i m . 2 0 1 3;2 8(2):57-60 Reprodução & Climatério h t t p : / / w w w . s b r h . o r g . b r / r e v i s t a informações sobre o artigo Histórico do artigo: Recebido em 25 de junho de 2013 Aceito em 14 de agosto de 2013 Palavras-chave: Infertilidade Reprodução humana Prevenção r e s u m o Objetivo: O estudo foi feito a fim de avaliar o conhecimento e a prática de medidas preventivas em infertilidade. Método: Durante um mês foi aplicado um questionário às pacientes que frequentam o Ambulatório… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…As to the use of alcoholic beverages and smoking, these findings were different relative to those of other studies, (3,9,25) that observed an interference of these einstein (São Paulo). 2020;18:1-5…”
Section: ❚ Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…As to the use of alcoholic beverages and smoking, these findings were different relative to those of other studies, (3,9,25) that observed an interference of these einstein (São Paulo). 2020;18:1-5…”
Section: ❚ Discussioncontrasting
confidence: 95%
“…The lack of knowledge about infertility hinders the adoption of preventive measures in its treatment. (9) Obesity, and primarily abdominal obesity, participates in this etiology, and the awareness of its relation with infertility is extremely important, so that the nutritional status of subfertile women, that is, women with absence of conception who actively want to conceive, can be corrected. (10) Ovulatory defects and inexplicable causes represent more than 50% of etiology of infertility (11) and, although not the only factors involved, one should carefully analyze the ovulatory issues with the intention of positive reversal for a fertility process.…”
Section: ❚ Introductionmentioning
confidence: 99%